2010
DOI: 10.1007/s00330-010-1933-1
|View full text |Cite
|
Sign up to set email alerts
|

CT colonography and transient bacteraemia: implications for antibiotic prophylaxis

Abstract: American Heart Association and National Institute for Clinical Excellence guidelines advise that antibiotic prophylaxis before lower gastrointestinal endoscopy is not indicated in patients with at risk cardiac lesions (ARCL) as the risk of a transient bacteraemia leading to infective endocarditis is low. These data show that the prevalence of transient bacteraemia after CTC is also low. It follows that patients with ARCL do not require antibiotic prophylaxis before CTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In some studies on bacteremia after an endoscopic procedure, the incidence of transient bacteremia was 4.3-31.9% [12][13][14] . In another study, the estimated significant bacteremia rate after a CT colonography is 0-3.7% 15 . In a study by Sharif-Kashani et al , after a flexible fiberoptic bronchoscopy, transient bacteremia occurred in 1 patient (1.1%) and fever in 9 patients (10.5%) in the first 24 hours 16 .…”
Section: ⅳ Discussionmentioning
confidence: 93%
“…In some studies on bacteremia after an endoscopic procedure, the incidence of transient bacteremia was 4.3-31.9% [12][13][14] . In another study, the estimated significant bacteremia rate after a CT colonography is 0-3.7% 15 . In a study by Sharif-Kashani et al , after a flexible fiberoptic bronchoscopy, transient bacteremia occurred in 1 patient (1.1%) and fever in 9 patients (10.5%) in the first 24 hours 16 .…”
Section: ⅳ Discussionmentioning
confidence: 93%
“…However, a retrospective study of patients aged over 70 years demonstrated no significant changes in serum urea, sodium, potassium, or estimated glomerular filtration rate when using sodium picosulfate-magnesium citrate catharsis prior to CTC [37]. Finally, although it has been suggested that bacteria introduced during colonography could risk infection of prosthetic vascular grafts, a study of 100 consecutive patients subject to serial blood cultures following CTC failed to showed significant bacteremia, and suggested antibiotic prophylaxis is not required [38].…”
Section: Safetymentioning
confidence: 91%